Theorizing Radical Practice: Community Arts and Transformative Learning - Michelle Glowacki-Dudka; Brid Connolly (Adult Education Research Conference, 2014)
This roundtable presentation provides an exploration of the role that creative, critical teaching and learning could play in addressing social and personal suffering through reflective practice, expressive ways of knowing and cultural resistance. It will draw on Freirean pedagogy, and feminist, critical and community theory to propose the way ahead.